IMPLEMENTING DIFFERENTIATED INSTRUCTION IN INDONESIAN SECONDARY SCHOOLS: OPPORTUNITIES AND CHALLENGES FROM LANGUAGE TEACHERS - Tundreng, Syarifuddin; Yawan, Hendri; Marhamah, Marhamah (University of Kuningan, 2025)
The implementation of differentiated instruction (DI) is significant, as Indonesia's new curriculum emphasizes its role in enhancing student learning outcomes and accommodating diverse learning needs. This study employs a qualitative case study approach to explore the teachers’ understanding, benefits and challenges in implementing Di within language classroom. The research involved five teachers from three public secondary schools in Indonesia, all with a minimum of five years of teaching experience. Data collection encompassed multiple ways, including semi-structured interviews, classroom observations, and document analysis, following a thematic analysis framework. Findings revealed that while teachers recognized the benefits of DI in fostering student engagement and catering to diverse learning needs, they faced challenges such as time constraints for preparation, varying levels of student responsiveness, and difficulties in obtaining parental support, which hindered the overall effectiveness of instruction. This research contributes to the discourse on DI in education by highlighting practical insights for enhancing teaching practices and addressing the complexities involved in meeting diverse student needs.